2006
DOI: 10.1111/j.1439-0426.2006.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history of the red-banded seabream Pagrus auriga (Sparidae) from the coasts of the Canarian archipelago

Abstract: Red-banded seabream Pagrus auriga (N ¼ 615) were caught off the Canary Islands from January 2003 to December 2004. Total length ranged from 120 to 780 mm. The species was characterized by protogynous hermaphroditism. The male : female ratio was in favour of females (1 : 8.2). The reproductive season extended from September to February, with a peak in spawning activity in October-November. Fifty percentage maturity was reached at 387 mm total length by females and 533 mm by males. The length-weight relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Previous studies found that fish hooked in deeper waters presented more severe signs of barotrauma and, consequently, had higher mortality rates (Götz et al, 2007;Alós, 2008;Sumpton et al, 2010). Therefore, our results should not be applied to boat fishing for example, particularly when a fish is hooked at greater depths (>30 m) (Pajuelo et al, 2006). Another potentially important factor for recreational shore fishing is the height from which the fish are released back to the sea.…”
Section: Parametersmentioning
confidence: 84%
“…Previous studies found that fish hooked in deeper waters presented more severe signs of barotrauma and, consequently, had higher mortality rates (Götz et al, 2007;Alós, 2008;Sumpton et al, 2010). Therefore, our results should not be applied to boat fishing for example, particularly when a fish is hooked at greater depths (>30 m) (Pajuelo et al, 2006). Another potentially important factor for recreational shore fishing is the height from which the fish are released back to the sea.…”
Section: Parametersmentioning
confidence: 84%
“…Also, in a review of otolith studies including 94 species from 36 families, Beckman and Wilson (1995) found that, for the majority of the low latitude species studied, the period of opaque growth coincided with summer months, and they also concluded that opaque zone deposition is partially related to local increases in temperature, but that the controlling factors are a combination of environmental and endogenous factors. The variable size of the first annulus formed during the first winter following hatching is presumed to be functions of both the protracted redbanded seabream spawning season (Pajuelo et al, 2006) and the rapid growth rate of juvenile. Those individuals that are spawned early in the season will experience proportionally more growth (and presumably more hyaline zone accretion adjacent to the otolith core) than will a late spawned individual; thus, the first annulus will be more distant from the otolith core in the former instance than under the latter circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…Individual ages were corrected by the birthdate, corresponding to the mid-point of the spawning period (Pajuelo et al, 2006) and taking into account the date of capture. Thus is, 1 December was considered as birthdate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the Canarian fishing fleet shows a high social and economic dependency on small-scale fishing (FAO 2011;EU Fisheries in Canary Islands 2013). The assessment and further management of these resources is complicated, because the knowledge of biological parameters is restricted to the main commercial species (González and Lozano 1992;Pajuelo and Lorenzo 1995, 1999García-Díaz et al 1997Méndez-Villamil et al 1997;Pajuelo et al 2006;González et al 2012). Importantly, there are no available historical, temporal, series of catches and fishing effort for all gears and ports (Hernández-García et al 1998), what avoid proper evaluation of fishing trends through decades.…”
Section: Introductionmentioning
confidence: 99%